Mandapa (pillared hall) of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is the north-facing lateral transept that is attached to the mandapa (pillared hall) of the Mahanaleshwar Temple. The plinth of this transept had a chamber with a narrow opening to it. This plinth had four pillars that supported the cantilevered roof of the transept. The inner pillars on the plinth are flanked by perforated jalis (latticed windows). The use of these chambers in the basement cannot be ascertained. But they are commonly found in the temples of this region and time period. These possibly served as spaces for meditation.